A deontic possibility modal in Latvian: Personal vs. impersonal uses in a corpus - Daugavet, Anna (Vilnius University Open Series, 2021)
A corpus-based study of a dedicated deontic possibility modal in Latvian focuses on its impersonal variety with a non-canonical subject in the dative. Normally, drīkstēt ‘may’ and other possibility modals have nominative subjects, while dative subjects are found with expressions of necessity. As distinct from other constructions where non-canonical dative subjects are experiencers, the modals are also used with inanimate subjects.A frequent ellipsis of lexical verbs in the impersonal uses of drīkstēt not only reflects the informal style of the construction but also points to the Russian možno / nel’zja as a possible source, especially when combined with an object in the accusative referring to food. The Russian construction has a meaning of deontic possibility, but its use is restricted to animate subjects. The article claims that the animacy restriction was lifted in Latvian under the influence of the necessity modals in contexts of prohibition.
Keywords: Baltic; Latvian; modals; deontic possibility; impersonal; non-canonical subjects